First Contemporary Case of Human Infection with Cryptococcus gattii in Puget Sound: Evidence for Spread of the Vancouver Island Outbreak - Upton, Arlo (American Society for Microbiology, 2007)
We report a case of cryptococcosis due to C. gattii which appears to have been acquired in the Puget Sound region, Washington State. Genotyping confirmed identity to the predominant Vancouver Island genotype. This is the first documented case of human disease by the major Vancouver Island emergence strain acquired within the United States.